Review Article about Dye-Sensitized Solar Cells and their Applications - Shakar, Fatima Najah Ismail; Jawad, Zahraa Raheem Abd Alzahra; Hiadar, Lara Salah Ibrahim; Dalaf, Aeisha Rushdi Nawar; Saleh, Ghadeer Nasser Mahdi (American Journal of Botany and Bioengineering, 2025)
Dye-sensitized solar cells (DSSCs) are low-cost, readily available, and nontoxic photovoltaics based on abundant materials that can be fabricated as thin, lightweight flexible solar panels. When DSSCs are used to harvest indoor lighting, they are efficient in generating the energy required for powering energy-hungry electronic applications such as wireless sensors. Nonetheless, this vast market has remained untapped for decades, replete with opportunities for producing inexpensive indoor solar panels. The review summarizes the DSSC material research trends beyond the most used commercial benchmark TiO2-based architecture and cobalt-based electrolytes. The stars among the newly investigated electrode materials are metal oxide scheduling cation-doped ZnO and SnO2 at the same time, carbon-based dyes, and polymeric redox mediators. Rapid progress has been made with new and optimized materials that increase the photovoltaic performance of DSSC devices. Importantly, these alternative materials provide the foundation for advancing DSSC designs where all component materials are researched and fabricated as a single device structure. First, a window-layer-less competitive photoanode architecture is presented where metal oxide film, counter electrode, and electrolyte are integrated in the same operating procedure. Then, a flat glass substrate with a photoanode film on one side is presented, leading to a transparent, colorless, or colored indoor solar panel without interfaces to shield the following front or back sides. This review highlights DSSCs as a vibrant and diverse field of research from the perspective of recent material development trends that aim for the mass production of next-generation DSSCs. Attention is directed outward toward accommodating new materials, methods, and architectures for DSSCs. However, a strong foundation is left to work from, covering the state-of-the-art DSSC material choices and suggesting procedures for their implementation in the mass production of next-generation DSSC devices. Many opportunities remain to grow from here and, at the same time, to delve deeper into the materials presented, as many are still far from their maximum potential. Although the rapidly developing polymers and carbon-based materials likely represent the forefront of DSSC research, there should still be surprises and new findings with the well-known and most-studied metal oxide past players. Future discussions on battery and supercapacitor device prototypes containing DSSC are anticipated, as the devices comprise, in essence, a wide redox potential window of adsorbents, and redox mediators investigated as possible new dye-sensitized battery chemistries.